Güneydoğu Anadolu Bölgesindeki Insani Kalkınma Düzeyi - Hakan Mıhçı (Turkish Economic Association, 2012)
– The main aim of this study is to determine current human development level of Southeastern Anatolia region which is one of the least developed regions of Turkey. To reach this aim, main human development indicators are being analyzed depending on the global and national human development reports. This analysis is focused on the provinces of the region. Almost all the provinces of the region held the lowest human development indicators of the country, and they have not been able to change their relative position through time. Therefore, the provinces within the Southeastern Anatolia region, with the possible exception of Gaziantep province, did not only remain below the country averages but they also ranked considerably far away from the international human development standards. If we consider socio-economic development level of the provinces within the region, we can also face with the same picture. As a matter of fact, it might be emerged that the region is the one which, at most heavily, deals with the property problems. Besides, significant portion of the observed human development problems in the provinces of Southeastern Anatolia Region is originated from the gender differences. Compared with men, women are relatively in worse position with respect to both education and per capital income levels. But, at the same time, this situation creates an opportunity to enhance human development level of the region. The national human development performance might relatively be improved as long as the gender differences could be reduced.
Keywords: 330; Development; Human Development; Human Development Index; Southeastern Anatolia Region; Human Poverty